Let the sunshine in [videorecording (DVD)] - Denis, Claire, 1948-; Denis, Claire, 1948-; Binoche, Juliette, 1964-; Beauvois, Xavier; Katerine, Philippe, 1968- (Criterion collection, 2019)
A divorced mother and artist living in Paris looks for true love.